2015
DOI: 10.1039/c4ra15335a
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally benign antifouling potentials of triterpene-glycosides from Streptomyces fradiae: a mangrove isolate

Abstract: In the present study, an attempt has been made to screen and evaluate the antifouling potentials of the actinobacterial strainStreptomyces fradiaeRMS-MSU isolated from the manakkudy mangroves of Tamilnadu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
(47 reference statements)
1
14
0
2
Order By: Relevance
“…The antifouling nanocarrier technology provides controlled release of the active compounds, enabling the target foulers to be effectively addressed, along with a relatively low release of the compounds into the ambient waters [45]. Mussels have been successfully used as a model system to test the antifouling activity of biocidal compounds by determining both their continued attachment by byssus threads and their mortality [26,27,46]. Similarly, the commonly employed model system-larvae of B. neritina, has been used to determine antifouling efficacy [28,29].…”
Section: Model Systems In Geographic Perspectivementioning
confidence: 99%
“…The antifouling nanocarrier technology provides controlled release of the active compounds, enabling the target foulers to be effectively addressed, along with a relatively low release of the compounds into the ambient waters [45]. Mussels have been successfully used as a model system to test the antifouling activity of biocidal compounds by determining both their continued attachment by byssus threads and their mortality [26,27,46]. Similarly, the commonly employed model system-larvae of B. neritina, has been used to determine antifouling efficacy [28,29].…”
Section: Model Systems In Geographic Perspectivementioning
confidence: 99%
“…Application of antifouling compounds from natural sources is considered as one of the best replacement options for the antifouling processes [79]. A wide variety of marine natural products from seagrasses, seaweeds, mangroves, coral reefs, sponges and their associated organisms proved to be an excellent source of bioactive compounds and a wide range of secondary metabolites, many of which exhibited a broad spectrum of antifouling activity against marine biofilm forming microbes, algal spore adherence, mussel (phenoloxidase activity) and barnacles to artificial substratum [80]. Previous reports demonstrated that ZnO, CuO and AgNPs coated on solid surfaces inhibit the biofilm formation [76][77][78] and particularly AgNPs act as potential antimicrobial agents against different marine biofilm forming microorganisms [44].…”
Section: Antifouling Propertiesmentioning
confidence: 99%
“…Factors such as fluctuations in salinity and tidal gradient are believed to be the driving force for metabolic adaptations, which could in turn lead to production of valuable metabolites. In fact, the growing interest in bioactive potentials of mangrove-derived Streptomyces has been demonstrated by the isolation of Streptomyces pluripotens (Lee et al, 2014a ), S. fradiae (Prakash et al, 2015 ), S. cheonanensis (Mangamuri et al, 2016 ), and S. malaysiense (Ser et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%